DEVELOPMENT AND VALIDATION OF A RP-HPLC METHOD FOR ESTIMATION OF TELMISARTAN IN HUMAN PLASMA - Ashok, P.; Narenderan, S. T.; Meyyanathan, S. N.; Babu, B.; Vadivelan, R. (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study was aimed to develop a rapid, specific and sensitive method based on high performance liquid chromatographic method was developed for the determination of telmisartan using indapamide as an internal standard. Methods: The utilization of single step protein precipitation method using methanol as a precipitating agent becomes suitable for analysis of a large number of samples. The developed method was validated as per US-FDA guidelines for telmisartan in human plasma. Result: An isocratic separation was achieved using Hibar C18 (250 x 4.6 mm, 5 μm) column using 10 mmol ammonium formate solution (pH 4.0)–methanol (70:30, v/v) as the mobile phase. Detection was carried out at 275 nm. The method was validated over the range of 0.1–1.5 µg/ml in human plasma with a regression analysis of 0.996. The percentage recovery of the present method was found to be 94.0–99.2 %. Conclusion: The developed analytical method was found to be rapid, single step, plasma preparation coupled with the simple high-performance liquid chromatography coupled with UV detection (HPLC–UV) isocratic chromatographic apparatus makes the method cost-effective and suitable for analysis of a large number of samples.